2015
DOI: 10.5296/jbls.v6i1.6615
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Toxicological Studies of an Extract of the Seeds of Picralima Nitida (Stapf) (Apocynaceae) and Its Pharmacological Effects on the Blood Pressure of Rabbit

Abstract: The phytochemical screening of the seeds extracts of Picralima nitida has highlighted the presence of alkaloids and terpenes poly sterols in chloroform solutions, methanol and in the aqueous. Unlike chloroform and methanol solutions, the aqueous revealed the presence of saponins. An acute toxicity study in mice showed that the aqueous extract of Picralima nitida would be slightly toxic with a lethal dose (LD) 50 % of 9120.11 mg/kg of body weight (bw). This extract, in rabbits induced a dose-dependent hypotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It was determined from the safety studies that PNE has an LD 50 >2000 mg/kg. This safety profile has also been established in a study by N’dri in which a phytochemical and toxicological study was conducted on the seed extract of P. nitida where the LD50 was about 9000 mg/kg ( 65 ). This obviously speaks well of the safety of the extract.…”
Section: Discussionmentioning
confidence: 88%
“…It was determined from the safety studies that PNE has an LD 50 >2000 mg/kg. This safety profile has also been established in a study by N’dri in which a phytochemical and toxicological study was conducted on the seed extract of P. nitida where the LD50 was about 9000 mg/kg ( 65 ). This obviously speaks well of the safety of the extract.…”
Section: Discussionmentioning
confidence: 88%
“…However, this corroborates the findings of Sylvester, et al . (2015) on G. latifolium and N’dri (2015) on P. nitida.…”
Section: Discussionmentioning
confidence: 98%
“…Gongronema latifolium (GL) which belongs to family Apocynaceae, Subfamily Asclepiadoideceae is a climbing perennial plant that is edible with sharp, bitter and slightly sweet taste, especially when eaten fresh. It is commonly known as Amaranth globe or Bush busk, locally called 'utazi' in South eastern Nigeria and 'Arokeke' or 'Madunmaro' in South western Nigeria (Eleyinmi, 2007;Nazia et al, 2013). G. latifolium has been reported for its antibacterial activity (Eleyinmi, 2007;Enyi-Idoh et al, 2017), anticancer (Iwea-la, 2015, hepatoprotective effects (Imo, 2017;Aloke, Ogbodo and Ejike, 2018), hypoglycemic and hypolipidemic activities (Sylvester, et al, 2015;Eyo & Chukwu, 2016) due to its different active constituents.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ngassona et al [55] found terpenoids in polar extracts of the barks of the trunk and the root of Picralima nitida in addition to the previously described phyto-compounds. The seeds of the species discovered in Ivory Coast were also found to contain terpenoids and alkaloids [53,56,57]. Akuammine, akuammidine, akuammicine, akuammine, and pseudoakuammine are among the noteworthy indole alkaloids with opioid analgesic activity that have been discovered from the seeds of P. nitida [16].…”
Section: Discussionmentioning
confidence: 99%